Citrus Seed Oils Efficacy against Larvae of Aedes aegypti - Hazrat Bilal; Waseem Akram; Soaib Ali Hassan; Sadur Din (Tehran University of Medical Sciences, 2017)
Background: Dengue fever is a serious public health issue in Pakistan for many years. Globally plants have been reported to contain compounds with insecticidal properties. These properties have been demonstrated more recently on the larval stages of mosquitoes. Therefore, Citrus cultivar seeds were evaluated for larvicidal potential against the primary dengue vector Aedes aegypti. Methods: Extraction of oil was done by a steam distillation method and oils were evaluated according to WHO guidelines for larvicides 2005 for evaluation of insecticidal properties of citrus seed extracts against mosquito larvae. Result: Among the Citrus cultivar seed oil, rough lemon (Citrus jambhiri) had the lowest LC50 value (200.79ppm), while musambi (C. sinensis var musambi) had the highest LC50 value (457.30ppm) after 24 h of exposure. Conclusion: Citrus cultivars have some larvicidal potential but C. jambhiri had the greatest potential against A. aegypti larvae. Further small-scale field trials using the extracts of C. jambhiri will be conducted to determine operational feasibility.